Single Cell Analysis of Endothelial Cells Identified Organ-Specific Molecular Signatures and Heart-Specific Cell Populations and Molecular Features - Feng, Wei; Chen, Lyuqin; Nguyen, Patricia K.; Wu, Sean M.; Li, Guang (Frontiers in Cardiovascular Medicine, 2019)
The endothelial cell exists in the whole body by lining the inner surface of vasculature and plays an important role in normal physiology and disease progressions. Each organ should have a heterogeneous population of endothelial cells, but these heterogeneities have not been systematically analyzed at single cell level. The Tabular Muris project profiled mouse single cells from 20 organs, which includes endothelial cells in 10 organs. Unsupervised analysis of these endothelial cells found they were mainly grouped by organs, and each organ-specific cells were further partially correlated by germ layers. Unexpectedly, all lymphatic endothelial cells were found to group together regardless of their organ sources. To further understand the cellular heterogeneity in organ-specific endothelial cells, we used the heart as an example. Heart as a pump of the circulation system has multiple types of endothelial cells. Detailed analysis of these cells identified an endocardial endothelial cell population, a coronary vascular endothelial cell population, and an aorta-specific cell population. Through integrated analysis with aorta single cell data in another two studies, we identified the cell populations and molecular markers that are conserved across all three studies. In summary, by reanalyzing the existing single-cell mRNA sequencing data, we identified organ-specific endothelial cell molecular signatures and heart-specific endothelial cell subpopulations and molecular markers. We expect these findings will pave the way to deeper understand the vascular biology and endothelial cell-related diseases.